Assessing the economic challenges posed by orphan drugs - Drummond, Michael F.; Wilson, David A.; Kanavos, Panos; Ubel, Peter; Rovira, Joan (International journal of technology assessment in health care, 2007)
Historically, patients with rare diseases have been underserved by commercial drug development. In several jurisdictions, specific legislation has been enacted to encourage the development of drugs for rare diseases (orphan drugs), which would otherwise not be commercially viable. However, because of the small market, these drugs are often very expensive. Under the standard methods of health technology assessment (HTA) incorporating economic evaluation, orphan drugs do not usually prove to be cost-effective and this, coupled with their high cost, means that funding and patient access may be limited. However, these restrictions may not be in line with societal preferences. Therefore, this study discusses whether the standard methods of HTA are adequate for assisting decisions on patient access to and funding of orphan drugs and outlines a research agenda to help understand the societal value of orphan drugs and issues surrounding their development, funding, and use.